1994
DOI: 10.1161/01.cir.90.2.959
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillar Ca2+ sensitization predominantly enhances function and mechanical efficiency of stunned myocardium.

Abstract: Calcium sensitization affects function and mechanical efficiency of stunned myocardium more profoundly than of not-stunned myocardium, lending support to the hypothesis that Ca2+ desensitization of the myofibrils is involved in myocardial stunning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…However, the pathophysiology of stunning in the pig appears to principally relate to altered calcium transients, rather than myofilament defects (20). On the other hand, one prior study using an alternative sensitizer reported enhanced responsiveness in stunned myocardium (39). However, substantial differences in heart rate with this agent may have contributed to this difference.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pathophysiology of stunning in the pig appears to principally relate to altered calcium transients, rather than myofilament defects (20). On the other hand, one prior study using an alternative sensitizer reported enhanced responsiveness in stunned myocardium (39). However, substantial differences in heart rate with this agent may have contributed to this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Others have hypothetized that especially during the late reperfusion phase, a decreased Ca 2+ sensitivity of myofilaments is involved in the contractile dysfunction, although mechanism(s) involved in the alteration of Ca 2+ activation of contractile apparatus were not provided [5]. This hypothesis of decreased Ca 2+ sensitivity is supported by a recent study from our laboratory in which we have shown that the Ca 2÷ sensitizing agent EMD 60263, which is devoid of phosphodiesterase inhibitor properties, restored segment length shortening and mechanical efficiency of stunned porcine myocardium, while exerting a negligible effect on the not stunned myocardium [49].…”
Section: Myocardial Stunningmentioning
confidence: 90%
“…In a recent report, Opie described as the two likely causes of stunning during the very early reperfusion phase excess of cystolic Ca 2÷ and the formation of free radicals [49]. For instance, it was shown that intracoronary Ca 2÷ infusions during stunning could restore the contractility [47].…”
Section: Myocardial Stunningmentioning
confidence: 99%
“…Despite numerous efforts, the cellular mechanism of myocardial stunning is not fully understood [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Stunned myocardium remains responsive to positive inotropic agents such as catecholamines [2], increased extracellular Ca 2+ concentration [3], phosphodiesterase III (PDE III) inhibitors (e.g.…”
Section: Introductionmentioning
confidence: 99%